Impact of Care Interventions on the Survival of Patients with Cardiac Chest Pain - Meneguin, Silmara [UNESP]; Pollo, Camila Fernandes [UNESP]; Jolo, Murillo Fernando [UNESP]; Sartori, Maria Marcia Pereira [UNESP]; de Morais, José Fausto; de Oliveira, Cesar (MDPI, 2023)
Background: Chest pain is considered the second most frequent complaint among patients seeking emergency services. However, there is limited information in the literature about how the care provided to patients with chest pain, when being attended to in the emergency room, influences their clinical outcomes. Aims: To assess the relationship between care interventions performed on patients with cardiac chest pain and their immediate and late clinical outcomes and to identify which care interventions were essential to survival. Methods: In this retrospective study. We analyzed 153 medical records of patients presenting with chest pain at an emergency service center, São Paulo, Brazil. Participants were divided into two groups: (G1) remained hospitalized for a maximum of 24 h and (G2) remained hospitalized for between 25 h and 30 days. Results: Most of the participants were male 99 (64.7%), with a mean age of 63.2 years. The interventions central venous catheter, non-invasive blood pressure monitoring, pulse oximetry, and monitoring peripheral perfusion were commonly associated with survival at 24 h and 30 days. Advanced cardiovascular life support and basic support life (p = 0.0145; OR = 8053; 95% CI = 1385–46,833), blood transfusion (p < 0.0077; OR = 34,367; 95% CI = 6489–182,106), central venous catheter (p < 0.0001; OR = 7.69: 95% CI 1853–31,905), and monitoring peripheral perfusion (p < 0.0001; OR = 6835; 95% CI 1349–34,634) were independently associated with survival at 30 days by Cox Regression. Conclusions: Even though there have been many technological advances over the past decades, this study demonstrated that immediate and long-term survival depended on interventions received in an emergency room for many patients.
Keywords: assistance; chest pain; critical care; emergency medical services; nursing